PENERAPAN PENDEKATAN PETA KONSEP UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 13 PEKANBARU - Deska Putri K; Hendri Mahardi; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract. This Research aim to to increase result of learning IPA class V SD Country student 013 Pekanbaru Teaching Year 2011/2012 through concept map Approach Applying. Subjek Research [is] class V SD Country student 013 Pekanbaru with student amount as much 32 people, consisted 19 men student people and 13 woman student people. This research Class Action Research consisted of 2 cycle. Cycle I consisted of 2 times the meeting by 1 daily restating times;rill, cycle to II consisted of 2 times the meeting by 1 [is] daily restating times;rill. Research instrument cover study peripheral ( Syllabus, RPP, LKS, Sheet Tes result of learning), sheet observation teacher activity and student activity. Data result of research analysed descriptively. Research data indicate that result learn student experience of improvement, before conducted action from 32 student people only as much 18 student people ( 56,25%) obtaining daily restating value above or [is] equal to Complete Criterion Minimize ( KKM). While as much 14 student people ( 43.75%) still below/under KKM. After conducted action [at] cycle I as much 81.25% student obtain;get daily restating value above KKM or equal to KKM, cycle to II as much 93.75% student obtain;get daily restating value above KKM. Student Activity [of] during Cycle I mean study process 80,34% with good category, and Cycle II mean 91,07 categorized Very Whether. From above clarification indicate that through concept map approach applying can improve result learn class V SD Country student mathematics 013 Pekanbaru, universe and earth itemsKeyword: Map Konsep,Hasil Approach Learn IPA1